Clinical diagnosis of phonological dyslexia in the school environment - a field study of 04 cases of students in the fourth year of primary school. - arabi, nesrine; ouldmohand, lamia (Journal of Social Sciences and Humanities, 2024)
The study aimed to diagnose cases of phonological dyslexia in the school environment, where the clinical approach was adopted using a case study method, on a sample of 4 cases ranging in age from 9 to 12 years old students of the fourth year of primary school, and to achieve the objectives of the study, the topic was addressed by dividing it into two procedural approaches: The first aims to control all the variables identified by the theoretical literature on this disorder, while the second aims to apply the diagnostic test for dyslexia. After collecting and analysing the data quantitatively and qualitatively, the results showed that all members of the study group suffer from a phonological pathway disorder during reading, which affected the reading of semi-words, in addition to making many phonological errors such as deletion, substitution, addition and distortion.